CIPP EVALUATION ON EMERGENCY ONLINE LEARNING DURING COVID 19 IN STKIP MNC - SANTOSA, IMAM; SUSENO, MUCHLAS; SETIADI, SYAMSI (Linguists : Journal of Linguistics and Language Teaching, 2022)
This study aims to evaluate the application of emergency online learning during covid 19 in STKIP Media Nusantara Citra using the CIPP evaluation model. The Context, Input, Process, and Product (CIPP) evaluation model was formed to identify the evaluation result for the sake of program improvement. The descriptive qualitative study was used in this research. The subjects of this research were the Director of STKIP MNC, the head of the quality control board, the vice director of STKIP MNC, The lecturers, the academic staff, and the students of STKIP MNC. The study utilized several instruments to gather the data; document analysis, observational checklist, questionnaire, and interview. The result of the study showed that in the context phase, the program was held based on a clear base: the Minister of Education and Culture letter No. 1 of 2020. In the input process. Moodle Learning Management system was the main component of delivering online learning. In the process stage, The Obstacles were internet networks and inadequate student-owned facilities, which are significant hurdles to the program's implementation. Moreover, the last phase, product evaluation, the use of LMS in online learning, eased the measurement of student participation in the program. However, the problems that appeared in the process evaluation must be the base of analysis in the future to ensure the sustainability of the hybrid learning program.